Aneurysmal SubArachnoid Hemorrhage—Red Blood Cell Transfusion And Outcome (SAHaRA): a pilot randomised controlled trial protocol. Issue 12 (7th December 2016) - English, Shane W; Fergusson, D; Chassé, M; Turgeon, A F; Lauzier, F; Griesdale, D; Algird, A; Kramer, A; Tinmouth, A; Lum, C; Sinclair, J; Marshall, S; et al.
Abstract : Introduction: Anaemia is common in aneurysmal subarachnoid haemorrhage (aSAH) and is a potential critical modifiable factor affecting secondary injury. Despite physiological evidence and management guidelines that support maintaining a higher haemoglobin level in patients with aSAH, current practice is one of a more restrictive approach to transfusion. The goal of this multicentre pilot trial is to determine the feasibility of successfully conducting a red blood cell (RBC) transfusion trial in adult patients with acute aSAH and anaemia (Hb ≤100 g/L), comparing a liberal transfusion strategy (Hb ≤100 g/L) with a restrictive strategy (Hb ≤80 g/L) on the combined rate of death and severe disability at 12 months. Methods: Design This is a multicentre open-label randomised controlled pilot trial at 5 academic tertiary care centres. Population We are targeting adult aSAH patients within 14 days of their initial bleed and with anaemia (Hb ≤110 g/L). Randomisation Central computer-generated randomisation, stratified by centre, will be undertaken from the host centre. Randomisation into 1 of the 2 treatment arms will occur when the haemoglobin levels of eligible patients fall to ≤100 g/L. Intervention Patients will be randomly assigned to either a liberal (threshold: Hb ≤100 g/L) or a restrictive transfusion strategy (threshold: Hb ≤80 g/L). Outcome Primary: Centre randomisation rate over the study period. Secondary: (1) transfusion threshold adherence; (2) study RBC transfusion protocol adherence; and (3) outcome assessment including vital status at hospital discharge, modified Rankin Score at 6 and 12 months and Functional Independence Measure and EuroQOL Quality of Life Scale scores at 12 months. Outcome measures will be reported in aggregate. Ethics and dissemination: The study protocol has been approved by the host centre (OHSN-REB 20150433-01H). This study will determine the feasibility of conducting the large pragmatic RCT comparing 2 RBC transfusion strategies examining the effect of a liberal strategy on 12-month outcome following aSAH. Trial registration number: NCT02483351 ; Pre-results.